STRUKTUR PENYAJIAN MUSIK TARI TOPENG TUNGGAL DALAM PERTUNJUKAN TOPENG BETAWI SANGGAR MARGASARI KACRIT PUTRA DI TAMBUN SELATAN KABUPATEN BEKASI - Gita Widiana Dewi, - (2023)
This research is titled "The Structure of Presentation of Topeng Tunggal Dance Music in Topeng Betawi Performance of Sanggar Margasari Kacrit Putra in South Tambun, Bekasi Regency". The issues and aims of this research are to describe and analyze the performance of the single mask dance, the role of the topeng tunggal dance music, and the composition of the topeng tunggal dance accompaniment music in the Betawi mask performance. This research used a descriptive analysis method with a qualitative approach. The data were collected through observation, interviews, documentation, and literature study. The results of this study showed that single-mask dance performances present people's lives through dance movements and plays, and also contain moral messages or social criticism conveyed in a subtle way. Topeng tunggal dance is a traditional art form that features dancers wearing three masks. This dance is usually performed during Betawi mask performances as the opening and identity of the show, along with music and singing. The role of music in this single mask dance performance serves as a dance accompaniment in which each waditra has its own role. The music composition of this topeng tunggal dance accompaniment consists of several parts, namely tatalu, panji mask accompaniment, samba mask accompaniment and jingga mask accompaniment. Keywords: Topeng Tunggal Dance, Performance, Music Composition, Sanggar Margasari Kacrit Putra.